Design of E-shaped Microstrip Patch antenna for S band Applications - Mr.P.Sivakumar,; P. Arunadevi,; Ms.T.Revathi,; Mr.L.K.Balaji Vignesh,; Mr.C.Shanmugaraja, (Journal of Electronic Design Engineering, 2019)
Micro strip antennas are widely used in many applications due to their low profile, low cost and ease of fabrication which is required in various applications like mobile & satellite communication, Global positioning system and wireless application etc. In this paper, different E-shaped micro strip patch antennas are designed and the results are compared. The antenna design is an improvement from previous research and it is simulated using ADS (Advanced Design System) software. The design has been made on low cost material of FR4 substrate having dielectric constant of 4.2 with thickness of 1.6 mm. The proposed scheme is used by the probe feeding technique in order to operate under the frequency range of 3.45 GHz. The main objective of this paper is to design E-shaped microstrip antenna under various conditions by adjusting the dimensions of the antenna. After comparing different antenna’s parameter values, the better antenna will give good enhancement in the return loss, bandwidth, gain and directivity.